DETEKSI DINI KETERLAMBATAN PERKEMBANGAN ANAK USIA DINI: KAJIAN LITERATUR - Nazirah Maulina; Fuji Hastuti; Faizatul Faridy; Nohan Suharni; Intan Ramadhani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Early detection of developmental delays is an important effort to ensure optimal growth and development during early childhood. Developmental delays that are not identified early may affect children's cognitive, language, motor, social-emotional, and adaptive abilities in the future. This study aims to examine various literature related to the importance, methods, indicators, and challenges of early detection of developmental delays in early childhood. The method used is a literature review by analyzing scientific articles, books, and research reports published between 2020 and 2025. The findings indicate that developmental screening through standardized instruments, parental observation, and collaboration among teachers, health workers, and families can improve the accuracy of identifying developmental problems. Early intervention after detection significantly contributes to improving developmental outcomes in children. Therefore, strengthening parents' and educators' understanding of developmental monitoring is essential to support children's developmental achievements.